2010
DOI: 10.1002/jbm.a.32786
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chemotactic and mitogenic response of SMCs to PDGF‐BB and FGF‐2 in fibrin hydrogels

Abstract: The delivery of growth factors to cellularize biocompatible scaffolds like fibrin is a commonly used strategy in tissue engineering. We characterized SMC proliferation and chemotaxis in response to PDGF-BB and FGF-2, alone and in combination, in 2-D culture and in 3-D fibrin hydrogels. While both growth factors induced an equipotent mitogenic response in 2-D culture, only FGF-2 was significantly mitogenic for SMCs in 3-D culture. Only PDGF-BB was significantly chemotactic in a modified Boyden chamber assay. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…28,35,37,52 It may be possible to delay TGF-b1 supplementation or deliver additional growth factors, such as platelet-derived growth factor (PDGF) and FGF, to promote SMC proliferation and collagen deposition. 53,54 Gong et al created a culture system for growing tissue-engineered blood vessels with human mesenchymal stem cells, where grafts were initially grown in medium supplemented with PDGF to encourage proliferation and collagen deposition, and then switched to TGF-b1. 28 This resulted in increased cell number and collagen deposition, as well as increased contractile protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…28,35,37,52 It may be possible to delay TGF-b1 supplementation or deliver additional growth factors, such as platelet-derived growth factor (PDGF) and FGF, to promote SMC proliferation and collagen deposition. 53,54 Gong et al created a culture system for growing tissue-engineered blood vessels with human mesenchymal stem cells, where grafts were initially grown in medium supplemented with PDGF to encourage proliferation and collagen deposition, and then switched to TGF-b1. 28 This resulted in increased cell number and collagen deposition, as well as increased contractile protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34] The use of proangiogenic, degradable hydrogels through the combination of angiogenic growth factors (GFs), such as the plateletderived GF (PDGF-BB) and vascular endothelial GF (VEGF), and biomaterials is an attractive approach that has shown enhanced therapeutic effect over delivery of GF alone. [35][36][37][38] Given the importance of islet revascularization in graft efficacy, we sought to explore the potential use of proangiogenic hydrogels within PDMS scaffolds at an alternative transplant site. We evaluated the ability of fibrin-based PDGF-BB-containing hydrogels to enhance engraftment efficiency, as well as competency of both intradevice and intraislet vascularization, in a syngeneic mouse transplant model.…”
mentioning
confidence: 99%
“…However, treatment of cells with Slit2-N inhibited RASM cells migration by suppressing the expressions of WASP and Arp2/3 and consequent actin rearrangement [26] It has lately been found that SMCs cultured in fibrin hydrogels have a more robust chemotactic response to PDGF-BB compared with FGF-2 [27]. Growth factors (GFs) have remarkable interactions with nonproteoglycan extracellular matrix proteins.…”
Section: Differential Pdgfr Expression In Vascular Smooth Muscle Cellsmentioning
confidence: 99%